1993
DOI: 10.1002/ana.410330126
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a lambert‐eaton myasthenic syndrome antigen

Abstract: Lambert-Eaton myasthenic syndrome is a paraneoplastic neuromuscular disorder in which an immune response directed against a small-cell lung tumor crossreacts with antigens in the neuromuscular junction. To isolate and characterize the antigens, we screened a human fetal brain expression library with a high-titer serum from a patient with Lambert-Eaton myasthenic syndrome. This screening resulted in the isolation of a complementary DNA clone encoding an antigen we call myasthenic syndrome antigen B (MysB). Appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0
1

Year Published

1994
1994
2009
2009

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 39 publications
0
28
0
1
Order By: Relevance
“…Our findings also confirmed that the short N-terminal region was important for modification of inactivation kinetics, because ␤ 2a and ␤ 2c subunits were only different in this region. The N-terminal region of the rat ␤ 2c subunit was identical to those of a Lambert-Eaton myasthenic syndrome antigen and the human ␤ 2c subunit, except for some amino acids considered to be species differences (23,30). The similarity to the former protein raises the possibility that the rat ␤ 2c subunit was cloned from neuron, which innervated into heart.…”
Section: Discussionmentioning
confidence: 80%
“…Our findings also confirmed that the short N-terminal region was important for modification of inactivation kinetics, because ␤ 2a and ␤ 2c subunits were only different in this region. The N-terminal region of the rat ␤ 2c subunit was identical to those of a Lambert-Eaton myasthenic syndrome antigen and the human ␤ 2c subunit, except for some amino acids considered to be species differences (23,30). The similarity to the former protein raises the possibility that the rat ␤ 2c subunit was cloned from neuron, which innervated into heart.…”
Section: Discussionmentioning
confidence: 80%
“…Some patients' antibodies also recognize cytoplasmic antigens (Viglione et at. 1992) which may be the fl-subunit of the Ca2+ channel (Rosenfeld et al 1993). …”
Section: Discussionmentioning
confidence: 99%
“…Following the discovery of anti-GAD antibodies in SMS, a series of antibodies against intracellular presynaptic nerve (47).…”
Section: Nerve Terminal/vesicle-associated Antigensmentioning
confidence: 99%